Baculovirus vectors in experimental geneand vaccine therapy - Solomko, A.P.; Zaharuk, O.A.; Chaschina, L.I.; Strokovskaya, L.I. (Вiopolymers and Cell, 2011)
The article provides a brief overview of the literature on target design, exploration properties and effectiveness of the application of recombinant baculoviruses in model systems in vivo. The results of experiments with wild and recombinant baculoviruses are analysed in regard to the priority areas of biomedicine such as tissue regeneration, gene therapy of cancer, development of vaccines against infe tious diseases and malignancies. Keywords: baculovirus, gene- and immunovector, mammals, system in vivo.